Fault Management Techniques to Enhance the Reliability of Power Electronic Converters: An Overview - Saeed Rahimpour; Oleksandr Husev; Dmitri Vinnikov; Naser Vosoughi Kurdkandi; Hadi Tarzamni (IEEE Access, 2023)
The reliability of power electronic converters is a major concern in industrial applications because of using prone-to-failure elements such as high-power semiconductor devices and electronic capacitors. Hence, designing fault-tolerant inverters has been of great interest among researchers in both academia and industry over the last decade. Among the three stages of fault management, compensating the fault is the most important and challenging part. The techniques for fault compensation can be classified into three groups: hardware redundancy methods which use extra switches, legs, or modules to replace the faulty parts directly or indirectly, switching states redundancy methods which are about omitting and replacing the impossible switching states, and unbalance compensation including the techniques to compensate for the unbalances in the system caused by a fault. In this paper, an overview of fault-tolerant inverters is presented. A classification of fault-tolerant inverters is demonstrated and major cases in each of its categories are explained.